A Study of Precision Current Efficiency Curve Measurement with a Casing-Type Anode - Hao Wang; Jia Liu; Di Zhu (Applied Sciences, 2021)
Electrochemical machining (ECM) is a non-traditional machining technology that is widely used in the manufacturing of key components in the aviation industry. The current efficiency is defined as the ratio of the observed amount of dissolved metal to the theoretical amount predicted from Faraday’s law. In ECM, the current efficiency curve relates the dissolution rate of the anode material and the current density. Accurate measurement of the current efficiency curve is the basis for anode shape prediction and cathode tool design. However, in conventional measurement methods, the phenomenon of edge stray corrosion introduces significant measurement errors. Improving the current efficiency is thus a challenging task for any electrophysical or electrochemical machining process. To improve the measurement accuracy, this paper proposes a current efficiency curve measurement with a casing-type anode. In the proposed measurement method, the anode is designed in two parts: the mandril and the casing. The edge stray corrosion effect is mainly concentrated on the casing, and only the current distribution on the mandril is considered in the calculation of current efficiency. The measurement simulations of the conventional and the proposed methods were carried out. The simulation results show that the casing-type method significantly improves the accuracy of current efficiency measurements, and the current efficiency curve of 304SS was obtained.